2011
DOI: 10.1371/journal.pone.0024551
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Protection by Angiotensin Receptor Antagonism Involves Differential VEGF Expression in Both Hemispheres after Experimental Stroke

Abstract: We identified that the angiotensin receptor antagonist, candesartan, has profound neurovascular protective properties when administered after ischemic stroke and was associated with a proangiogenic state at least partly explained by vascular endothelial growth factor A (VEGFA). However, the spatial distribution of vascular endothelial growth factor (VEGF) isoforms and their receptors remained unknown. Protein analysis identified a significant increase in vascular endothelial grow factor B (VEGFB) in the cerebr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
56
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 22 publications
4
56
2
Order By: Relevance
“…Our findings show an increased expression of both isoforms in the ipsilateral and the contralateral hemispheres. Nevertheless, VEGF-A upregulation was more pronounced and lasted longer in the contralateral hemisphere, suggesting a role of this hemisphere in the process of recovery (Guan et al, 2011c). The increase in VEGF-B, on the other hand, was most pronounced at 8 hours in the ipsilateral hemisphere, consistent with its main role as a prosurvival factor.…”
Section: Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…Our findings show an increased expression of both isoforms in the ipsilateral and the contralateral hemispheres. Nevertheless, VEGF-A upregulation was more pronounced and lasted longer in the contralateral hemisphere, suggesting a role of this hemisphere in the process of recovery (Guan et al, 2011c). The increase in VEGF-B, on the other hand, was most pronounced at 8 hours in the ipsilateral hemisphere, consistent with its main role as a prosurvival factor.…”
Section: Discussionmentioning
confidence: 71%
“…This effect was evident by the ability of the CSF, collected at different time points, to transform brain endothelial cells into tube-like structures resembling blood vessels in vitro. Our previous work linked candesartan's beneficial effects to enhanced production of VEGF-A, the prototypical angiogenic molecule, as well as the relatively new VEGF isoform, VEGF-B (Guan et al, 2011c). The exact function of VEGF-B is still controversial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…90 Recently, we showed that the angiotensin II type 1 receptor antagonist, candesartan, when administered at reperfusion in a rat model of temporary MCAO, promoted recovery and angiogenesis in the contralesional striatum at 7 days after the stroke. 99 This was confirmed in a more recent investigation where normoglycemic rats showed increased angiogenesis and recovery after stroke compared with diabetic animals, where vascular regression after stroke accompanied a much poorer functional outcome. 100 In summary, angiogenesis occurs after stroke and is closely linked to recovery.…”
Section: Stroke and Neovascularizationmentioning
confidence: 63%
“…Of interest, the angiogenic response of candesartan was maintained even in nonstroked rats (Kozak et al, 2009). Subsequently, it was demonstrated that candesartan increased the expression of a number of genes for proangiogenic growth factors, including brain-derived neurotrophic factor (BDNF), after experimental cerebral ischemia (Guan et al, 2011). BDNF is a member of the neurotrophin family that is expressed in a number of cell types and has been shown to have potent neurogenic, neuroprotective, and angiogenic effects (Caporali and Emanueli, 2009;Greenberg et al, 2009).…”
Section: Introductionmentioning
confidence: 99%